Natural product nanofibers derived from Trichoderma hamatum K01 to control citrus anthracnose caused by Colletotrichum gloeosporioides - Pheaktra Phal; Kasem Soytong; Supattra Poeaim (My University, 2023)
Abstract The antifungal activity of Trichoderma hamatum K01 to control Colletotrichum gloeosporioides C01 was recorded. Pathogenicity of C. gloeosporioides C01 on citrus leaves was confirmed by the Koch postulate. T. hamatum K01 inhibited the colony growth and conidia production of C. gloeosporioides C01 by 70.55 and 79.07%, respectively. Crude extracts from T. hamatum K01 expressed an antifungal activity against C. gloeosporioides C01. The crude TK01-MeOH showed the most potent inhibitory effect on the colony growth and conidia production at the ED 50 values of 273 and 355 ppm, respectively. Nanofiber TK01M gave the highest inhibition on the colony growth and conidia production at the ED 50 values of 13 and 3 ppm, respectively. Control mechanism was related to the major pyrone metabolite group (6-pentyl-2 H -pyran-2-one), organic compounds (benzoic acid, hexadecane, tetracosane), fatty acids (palmitic acid, linoleic acid, tetradecanoic acid, pentadecanoic acid, hexadecenoic acid, ethyl ester, linoleic acid ethyl ester, and ethyl oleate), and sorbicillin from GC-MS analysis, which were produced by T. hamatum K01. It is reported for the first time to isolate secondary metabolite pyrone (6-pentyl-2 H -pyran-2-one) from T. hamatum K01, and the first report of nanofibers constructed from T. hamatum K01 against C. gloeosporioides.
Keywords: Secondary metabolite; Allelopathy; Plant-Microbe Interactions and Immunity